Nylanderia of the World, Part IV: Taxonomic contributions to the American Clade I of New World Nylanderia (Hymenoptera: Formicidae) - Williams, Jason L.; Williams, John F.; Lapolla, John S.; Lucky, Andrea (Zootaxa, 2025)
Globally, potentially hundreds of Nylanderia species remain undescribed, hidden within several broadly distributed complexes of morphologically cryptic species. By integrating phylogenomics, geography, and morphology, we describe eight new Nylanderia species from southern Mexico and Mesoamerica, increasing the total number of known species in the genus to 131. In the Americas, Nylanderia is divided into two distantly related clades: American Clade I (AC1) and American Clade II (AC2). Within AC1, Nylanderia austroccidua (Trager) was originally described as a widespread and morphologically variable species distributed from Utah to Costa Rica. This species was diagnosed by a slight concavity in the anterior face of the pronotum and varying degrees of fine cuticular microsculpturing across the body that causes blue cuticular iridescence under microscopic examination. Using Ultraconserved Elements (UCEs) for molecular phylogenetic analysis, we found that taxa matching the original description of N. austroccidua are paraphyletic with respect to Nearctic Nylanderia species. We also found that AC1 includes a Neotropical subclade extending into Mesoamerica, the distribution of which overlaps with AC2, which is exclusively Neotropical. Along with an updated description of N. austroccidua, we also describe the following new species belonging to clade AC1: N. breviscapa, sp. nov., N. contraria, sp. nov., N. lazulina, sp. nov., N. luceata, sp. nov., N. mendax sp. nov., N. mosaica sp. nov., N. polita sp. nov., and N. usul, sp. nov. A dichotomous key and images of the worker caste of these species are included and, where available, images of queens and males are provided.